Removal of Nickel Ions from Aqueous Solutions by Using Insolubilized Humic Acid:Effect of pH and Temperature - BAKER, HUTAF; Hamzeh; Hanim, Abdel (Asian Journal of Chemistry, 2010)
A batch adsorption system using insolubilized humic acid was investigated to remove Ni(ll) from aqueous solutions in single component system at different temperature and pH values and at constant ionic strength. The experimental data were fitted to the Langmuir, Freundlich and Redlich-Peterson isotherm models to obtain the characteristic parameter of each model, in order to determine the best fit isotherm for each system. The Redlich-Peterson model was found to well represent the measured adsorption data. The results, which were analyzed by the three models showed temperature and pH dependence. The derived adsorption constants (log aL) and their temperature dependence from Langmuir isotherm have been used to calculate the corresponding thermodynamic quantities such as the free energy of adsorption, heat and entropy of adsorption. The thermodynamic data indicate that Ni(II) adsorption on to insolubilized humic add is entropically driven and characterized by physical adsorption.